CBDC and the Operational Framework of Monetary Policy - Jorge Abad; Galo Nu\~no; Carlos Thomas (Center for Economic Studies and ifo Institute (CESifo), 2024)
We analyze the impact of introducing a central bank-issued digital currency (CBDC) on the operational framework of monetary policy and the macroeconomy as a whole. To this end, we develop a New Keynesian model with heterogeneous banks, a frictional interbank market, a central bank with deposit and lending facilities, and household preferences for different liquid assets. The model is calibrated to replicate the main monetary and financial aggregates in the euro area. Our analysis predicts that CBDC adoption implies a roughly equivalent reduction in banks' deposit funding. However, this 'deposit crunch' has a rather small effect on bank lending to the real economy, and hence on aggregate investment and GDP. This result reflects the parallel impact of CBDC on the central bank's operational framework. For relatively moderate CBDC adoption levels, the reduction in deposits is absorbed by an almost one-to-one fall in reserves at the central bank, implying a transition from a 'floor' system –with ample reserves– to a 'corridor' one. For larger CBCD adoption, the loss of bank deposits is compensated by increased recourse to central bank credit, as the corridor system gives way to a 'ceiling' one with scarce reserves.
Keywords: E42; E44; E52; G21; 330; central bank digital currency; interbank market; search and matching frictions; excess reserves